National Culture and Bank Liquidity risk of MSc Banking & Finance - Ma, Jiajia (2022)
Liquidity is always a very important influencing factor for banks. It is crucial to maintain a high level of liquidity and a low level of liquidity risk. This article uses the Horsfield individualist cultural indicators and the collectivist indicators of the global project to analyse the cultural tendency to represent individualism. The essay uses a sample of the 50 largest commercial banks in each of 17 countries over a 15-year period from 2005 to 2020. The essay runs GLS random effects regressions on this panel data. The paper concludes that individualism in a country's national culture is significantly and positively associated with the liquidity risk of banks in that country. We finally suggest that countries should regulate bank liquidity risk to different degrees depending on their culture. Countries with a higher degree of individualism should be more aware of the potential for greater liquidity risk in banks and take the necessary measures to control it. In this way, the risks of banks can be reduced and the stability of banks and of the national economy can be ensured.